Regards sur le sexe - De Ganck, Julie (Sextant, 2013)
If sex is and has always been pointed out, if it carries a lot of fertile speech, it is also and perhaps paradoxically hidden, denigrated or even hypocritically forgotten. But this is an essential organ for all life. Its necessity but also the secrets that surround it give it a mysterious character filled with strength and fragility, multiple pleasures and pains. Fruit of the conference "Show this sex that I can not see! This volume takes an essentially historical look at sex, enriched by a film analysis. This meeting highlights how the delimitation of what is sexual organ or not varies in time, space and body, physical and psychic. More than the establishment of a geography of the sexual, the important thing is what the organs relate on the relations between, on the one hand, the models of sexuation and functioning of the sexuality and, on the other hand, the regulation social relations.